Evaluation of Adhesive Bonding of Lithium Disilicate Ceramic Material with Duel Cured Resin Luting Agents - Lambade, Dipti Pravin (J Clin Diagn Res, 2015)
Purpose: The purpose of this vitro study was to comparatively evaluate the adhesive bonding of dual cured resin luting agents with lithium disilicate ceramic material. Materials and Methods: Porcelain laminate veneers were prepared with lithium disilicate ceramic material i.e. IPS Empress II( E-Max Press). These laminates were bonded with RelyX ARC, Panavia F 2.0, Variolink II, Duolink and Nexus NX3.The porcelain laminates were etched with 9.6% hydrofluoric acid (Pulpdent Corporation) for one minute, washed for 15 sec with three way syringe and dried for 15 sec with air syringe. The silane (Ultradent) was applied with the help of applicator tip in a single coat and kept undisturbed for one minute. The prepared surfaces of the premolars were treated with 37% phosphoric acid (Prime dent) for 15 sec, thoroughly rinsed and dried as per manufactures instructions. The shear bond test was carried out on all samples with the Universal testing machine (Instron U.S.A.) The scanning electron microscopic study was performed at the fractured interface of representative samples from each group of luting agents. Result: In this study, the highest value of shear bond strength was obtained for NEXUS NX3 and the lowest for VARIOLINK II. Conclusion: The difference in bond strength can be interpreted as the difference in fracture resistance of luting agents, to which shearing load was applied during the shear bond strength test. It is inferred from this study that the composition of the luting agent determines the adhesive characteristics in addition to surface treatment and bonding surface area.